Preference of institutional changes in social and economic development - Mimo Draskovic; Delibasic Milica; Ivic Mladen; Oksana Chigisheva (Journal of International Studies)
S. Kuznets wrote that structural changes are the central element in the process of development and the most important part of the growth model. They can hinder the growth, if carried out too slowly or inefficiently, but they can also promote economic growth if the distribution of resources gets better. The article has presented the authors' attempts to present new approaches to modeling the institutional behavior of economic agents. Different approaches and views on economic growth and economic development in their application to institutional changes are considered. The descriptive method explains the hypothesis of the dominant role of social innovations (primarily institutional changes) in social and economic development. Significance of sociocultural capital in the context of contemporary knowledge economy is potentiated. The conclusion is that transition countries must use exemplary models and civilization achievements of institutional changes in developed countries.